ANALISIS PERANAN GURU DALAM MEMBINA KEDISIPLINAN BELAJAR SISWA KELAS IV DI SDIT ZAHRA ASY-SYIFA - Auffah Yumni; Ainul Masthura Azis (Universitas Negeri Medan, 2022)
Analysis of the Teacher's Role in Fostering Learning Discipline for Class IV Students at SDIT Zahra Asy-Syifa. The purpose of this study was to determine the level of discipline in class IV students through the role of the teacher at SDIT Zahra Asy-Syifa in semester II of the 2021/2022 school year. The subjects in this study were the school principal, homeroom teacher for class IV, some 28 class IV students. This study uses a qualitative methodology with a descriptive approach where the design can be improved at any time depending on the conditions and situation in the field. Then in the data collection process using three data collection techniques namely, participating observation, semi-structured interviews and documentation. As for the data analysis technique using descriptive analysis from Miles and Huberman which consists of data reduction, data presentation, and drawing conclusions. The results of the study reveal that: 1) there is a teacher's role in fostering student learning discipline, namely the teacher as a teacher, mentor, counselor, evaluator and model/exemplar; 2) It turns out that teachers are still having problems in instilling discipline in student learning as seen from two factors, namely: a) students and b) family and the surrounding environment; 3) The teacher makes several efforts in instilling discipline including: a) instilling exemplary behavior, b) giving rewards and punishments, c) reinforcing the application of the rules.